Evolusi Mata Uang Logam, Fiat Money hingga Uang Elektronik: Manakah yang Lebih Unggul? - Ummah, Dewi Roichatul; Khusnudin, Khusnudin (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to analyze the evolution of metal currencies in dinars and dirhams, fiat money to electronic currencies, namely e-money, and compare currencies superior to the three currencies and see people's preferences for currencies. Qualitative research with a literature study approach. The result is to find out the evolution of metal currencies in the form of dinars and dirhams, banknotes, and electronic money see the preferences of the Indonesian people towards the currencies used, and see the impact of using e-money. These results will show the public how the currency is superior in terms of intrinsic value, and socio-economic, and technological developments so that later the public will know which currency is good to use in transactions.